Assessing AMT implementations an empirical field study - Sohal, Amrik S.
The writer studies seven Australian companies who have introduced Advanced Manufacturing Techniques (AMT) and provides an interesting analysis of the data gathered.
This paper reports the results of a study carried out to assess a number of different AMT implementations in different organizations. A case study method of investigation was used, and the experiences of seven companies were documented. The analysis carried out on the data gathered is presented on the following : competitive priorities and company goals, reasons for adopting the new technology, planning and implementation procedures/issues, benefits achieved from the AMT investment and the difficulties and limitations associated with adopting the AMT. The critical factors in the adoption of AMTs are identified as : learning from the experiences of others, appointment of a champion, establishment of committees and project teams, on-going and on-the-job training, technical support for the users, and appropriate changes to the organizational structure and managerial responsibilities.
Keywords: AMT implementations